Identification of a new tadalafil analogue, dipropylaminopretadalafil, in a dietary supplement. Issue 6 (2nd June 2016) - Huang, Yen-Chun; Lee, Hui-Chun; Lin, Yun-Lian; Tsai, Chia-Fen; Cheng, Hwei-Fang
ABSTRACT: A novel tadalafil analogue in a dietary supplement was found by drug-adulteration screening and isolated by column chromatography and HPLC. Based on extensive 1D- and 2D-NMR and mass spectral analyses, the structure of this new compound was determined as 2-( N, N -dipropyl acetyl) 3-methyl 1-(benzo[d][1, 3]dioxol-5-yl)-3, 4-dihydro-1H-pyrido[3, 4-b]indole-3-carboxylate – its common name is dipropylaminopretadalafil. Graphical Abstract: